'In One Ear and Out the Other – It's a Lot to Take in': A Qualitative Study Exploring the Informational Needs of Patients with ANCA‐Associated Vasculitis. (9th July 2012) - Mooney, Janice; Poland, Fiona; Spalding, Nicola; Scott, D. G. I.; Watts, Richard A.
Abstract Objectives To explore the informational needs of patients with anti‐neutrophil cytoplasmic antibody‐associated vasculitis (AAV). Methods Three focus groups and eight one‐to‐one interviews were conducted with patients with AAV. A purposeful sample of 15 patients (ten female) [disease: three Churg–Strauss syndrome (CSS); nine granulomatosis with polyangiitis (GPA); one microscopic polyangiitis (MPA); two polyarteritis nodosa (PAN)] participated in the focus groups. Eight (five female) (disease: three CSS; four GPA; one MPA) participated in the one‐to‐one interviews. A semi‐structured interview guide was used to explore patients' experiences of informational needs. The focus groups and interviews were audio‐recorded and transcribed verbatim, and analysed using the framework technique. Results Emergent themes were: reaction to diagnosis, need for information on disease management and access to knowledgeable practitioners. When given the initial diagnosis, all patients described themselves as being too ill to take in information and that they later found it difficult to find information. Most information received at diagnosis was in the form of verbal information given by the hospital doctor. Patients wanted positive but truthful information in the form of a booklet. Conclusions Receiving the diagnosis of a rare, potentially life‐threatening disease and then dealing with its complex treatment causes anxiety and fear and can impede information retention and recall. Patients want information on diagnosis and treatment but this should be tailored to individual needs, including timing that is appropriate for them. All patients wanted the opportunity to discuss their illness and its management with a knowledgeable healthcare practitioner but also wanted printed forms of information to assimilate at their own pace. Copyright © 2012 John Wiley & Sons, Ltd.